A Standardized Postoperative Care Pathway Eliminates Emergency Department Utilization After Hemorrhoidectomy - Mahmood, Ali; Yaakovian, Michael; Ali, Aman Barkat; Mahmood, Aiva Mariam; Mahmood, Emaan Anya (British Journal of Healthcare and Medical Research, 2026)
Background: Excisional hemorrhoidectomy is associated with significant postoperative morbidity, including pain, bleeding, urinary retention, and patient anxiety, frequently resulting in unplanned emergency department (ED) visits. We describe a standardized perioperative and postoperative care pathway designed to minimize complications and eliminate ED utilization. Methods: A retrospective review was conducted of consecutive patients undergoing excisional hemorrhoidectomy at a large regional hospital–affiliated practice. The protocol emphasized meticulous intraoperative hemostasis, structured patient education, early postoperative communication, and risk stratification for urinary retention. Primary outcome was ED utilization within 30 days. Secondary outcomes included postoperative bleeding, urinary retention, and wound-related concerns. Results: Approximately 100 patients were included. There were zero ED visits within 30 days postoperatively. No patients experienced major postoperative hemorrhage requiring intervention. Urinary retention was anticipated and managed in the outpatient setting without ED referral. All patients demonstrated appropriate wound healing. Conclusion: A structured, education-driven postoperative care pathway can eliminate ED utilization following hemorrhoidectomy while maintaining excellent clinical outcomes. This model is reproducible and scalable across healthcare systems.